HUBUNGAN KEFASIHAN MEMBACA AL-QUR’AN TERHADAP KEMAMPUAN BERBAHASA ARAB SISWA MA DARUL IHSAN DDI MAKASSAR - Abd Rahim Razaq (Universitas Muhammadiyah Makassar, 2017)
The purpose of this study refers to two main things namely, to determine the role of students inreading the Qur'an and the ability of Arabic language learning students, as well as to review the extent of the relationship of the ability of their abilities to read Al-Qur‟an which would be actualized in Arabic ability of students in MA Darul Ihsan Ponpes DDI Makassar. This research is field research by using qualitative approach and analyzed descriptively qualitative, research was conducted in MA Darul Ihsan Ponpes DDI Makassar. The variables in this study were the eloquence of reading the Qur'an as a dependent variable and the ability of Arabic as a free variable. The population in this study was MA Darul Ihsan Pondok Pesantren DDI-Makassar, amount 55 people, while the samples used in this study amount 55 people or called the sampling population. While in analyzing the data, researchers used technical qualitative descriptive analysis. The results of this study indicated that the eloquence of students in reading Al-Qur‟an had a fairly close relationship to the ability in Arabic language students in schools MA Darul Ihsan Pondok Pesantren DDI-Makassar. This was evidenced by the statement of various stakeholders in the observations made by the author, whether the teachers of study and students of MA Darul Ihsan Pondok Pesantren DDI-Makassar. Keywords :read Al-Qur’an, fluent, Arabic